1996
DOI: 10.1007/bf01716096
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the tick-borne encephalitis virus (TBEV) in ticks in several federal “Länder” of Germany by means of the polymerase chain reaction (PCR) — Characterization of the virus

Abstract: The aim of the present study was to analyse the current epidemiological situation with respect to TBE in the new federal "Länder" of Germany and in Saarland through detection of the TBEV genome in unengorged ticks using an RT-PCR technique. 22,273 ticks (Ixodes ricinus) were collected in the five new "Länder" (and some in Bavaria and Baden-Württemberg) and divided into 294 pools. It was possible to detect TBEV RNA in six pools of ticks from Mecklenburg Western-Pomerania [4], Brandenburg [1], Thuringia [1] (and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
4

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 3 publications
2
7
0
4
Order By: Relevance
“…This investigation provides further direct evidence of TBEV in Brandenburg (northeastern Germany) and is in line with case reports on human TBE patients in Brandenburg (Sü ss et al 1996, Becker et al 2006, RKI 2009. Further, the results demonstrate that TBEV is endemic in Brandenburg and Saxony-Anhalt, federal states that have not been previously classified as risk areas.…”
Section: Discussionsupporting
confidence: 90%
“…This investigation provides further direct evidence of TBEV in Brandenburg (northeastern Germany) and is in line with case reports on human TBE patients in Brandenburg (Sü ss et al 1996, Becker et al 2006, RKI 2009. Further, the results demonstrate that TBEV is endemic in Brandenburg and Saxony-Anhalt, federal states that have not been previously classified as risk areas.…”
Section: Discussionsupporting
confidence: 90%
“…Our literature review identified 15 full articles, and six abstracts published only in conference proceedings. As two full papers and four abstracts repeated data published elsewhere, 15 studies were included in the present overview (Ramelow et al., 1993; Süss et al., 1996, 2004, 2006; Cisak et al., 2002; Holbach and Oehme, 2002; Oehme et al., 2002; Pietsch et al., 2002; Frimmel et al., 2010; Klaus et al., 2010; Kondrusik et al., 2010; Kubica‐Biernat et al., 2010; Kupča et al., 2010; Dobler et al., 2011; Wójcik‐Fatla et al., 2011). Over 50 000 ticks were tested in the identified studies.…”
Section: Resultsmentioning
confidence: 99%
“…In 1992, Süss et al analyzed 18,760 unengorged ticks subdivided into 260 pools using n-RT-PCR and southern blot hybridization. Two tick pools from the Darss peninsula (near the villages Ahrenshoop and Müggenburg) and three tick pools from the island of Usedom (the villages Ahlbeck, Schmollensee, and Koserow) were found to be TBEV-positive, and one sequence was published (IZ-11/92) [14, 16, 21] (Figure 1). In the aftermath of this study over 16,000 ticks were collected between 1993 and 2003 but none was found to be TBEV-positive, leading to the assumption that natural foci were extinct or only present at an extremely low level of activity (Health Department of the State of Mecklenburg-West Pomerania, unpublished data) [17].…”
Section: Discussionmentioning
confidence: 99%